Lectures on the electrical properties of materials - Solymar, L. (Laszlo) (Oxford science publications., 1993)
"These lectures, written in a particularly readable and accessible style, stress the fundamental ideas relevant to the understanding of the electrical properties of materials. Topics are selected so that the operation of devices having applications (or possible future applications) in engineering can be explained."--Back cover.